Different personality factors drive work and non-work creativity - Shaw, Amy; Yu, Qi (Frontiers in Psychology, 2023)
This study examined whether creativity at work and outside of work had the same (or different) Big Five personality antecedents. Results revealed that although self-reported personal creativity outside of the workplace was related to the Openness to Experience trait only, supervisor-rated work creativity was associated with Openness, Extraversion, and Conscientiousness, and that after controlling for the effects of Extraversion and Conscientiousness, Openness did not contribute incremental validity in predicting work creativity, whereas when the impact of Openness was controlled for, Extraversion and Conscientiousness incrementally contributed to the prediction. Therefore, the study supported that while creativity was consistently driven by Openness across settings, the predictive effects of other traits (i.e., Extraversion and Conscientiousness) on creativity varied in work and non-work environments. Study limitations and implications for research and practices are discussed.